Adapting for Inertia: Delivering Large Government ICT Projects in Australia and New Zealand - Grant Douglas (ANU Press, 2023)
Despite much learning and research over many decades, large ICT software projects have continued to experience poor outcomes or fallen short of original expectations—some spectacularly so. This is the case in the Australian and New Zealand public sectors, even though these projects operate within historically developed institutional frameworks that provide the rules, guidelines and controls, and aim to consistently improve outcomes. Something is amiss. In Adapting for Inertia, Grant Douglas questions the effectiveness of these institutional frameworks in governing large ICT software projects in the Australian and New Zealand public sectors. He also gauges the perspectives of a large number of actors in projects in both sectors and examines two case studies in detail. The main narrative to emerge is that the institutional frameworks are in a state of inertia: they are failing to adapt, owing to various institutional factors—all of which have public policy implications. Sadly, Douglas finds, this inertia is likely to continue. If there is difficulty in changing the capacity to govern, he proposes, policymakers should look to change the nature of what is to be governed.
Keywords: 320; Governance of government ICT projects; Institutional framework for government ICT projects; Public policy for government ICT projects; Large government ICT projects; Large ICT projects in the Australian and New Zealand public sectors